2012
DOI: 10.1021/ja305491t
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Route for the Synthesis of Azomethine Imines and β-Aminocarbonyl Compounds from Alkenes

Abstract: Cyclic azomethine imines possessing a β-aminocarbonyl motif are accessed from simple alkene and hydrazone starting materials. A thermal, concerted alkene aminocarbonylation pathway involving an imino-isocyanate intermediate is proposed and supported by DFT calculations. A notable feature of the process is the steric shielding present in the dipoles formed, which allows for facile purification of the products by chromatography or crystallization. In addition, a fluorenone-derived reagent is reported, which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…4) by the reaction of hydrazone derivatives 113 bearing ester or amide moieties at the N-atom with alkenes (aminocarbonylation) in the absence of a solvent or in a,a,a-trifluorotoluene (Scheme 46). 144,149,150 The generation of N,N H -cyclic azomethine imines from hydrazones and alkenes is a thermal concerted reaction proceeding via the formation of an imino isocyanate intermediate the existence of which was confirmed by quantum chemical calculations. 150 …”
Section: Methods For Generation Of Azomethine Imines and Their 1mentioning
confidence: 86%
See 2 more Smart Citations
“…4) by the reaction of hydrazone derivatives 113 bearing ester or amide moieties at the N-atom with alkenes (aminocarbonylation) in the absence of a solvent or in a,a,a-trifluorotoluene (Scheme 46). 144,149,150 The generation of N,N H -cyclic azomethine imines from hydrazones and alkenes is a thermal concerted reaction proceeding via the formation of an imino isocyanate intermediate the existence of which was confirmed by quantum chemical calculations. 150 …”
Section: Methods For Generation Of Azomethine Imines and Their 1mentioning
confidence: 86%
“…This is promoted by performing the reaction with an alkene under more drastic conditions or by using more stable hydrazone (see Scheme 51 and Table 2). 150 This feature of the reactivity of N,N H -azomethine imines may be best illustrated by the reaction between acylhydrazone 113h and two alkenes differing in the reactivity (N-phenylmaleimide and norbornene), furnishing polycyclic adduct 135 as a mixture of two diastereomers (a-135 : b-135 = 3 : 2) in high yield (Scheme 58). 150 Being a more reactive alkene, norbornene reacts to form, in the first step, 1,3-dipolar intermediate 136, which subsequently undergoes the [3+2]-cycloaddition yielding the final adduct 135.…”
Section: Scheme 57mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that amphoteric amino‐ and imino‐isocyanates can be formed in situ under mild conditions and engage in high‐yielding alkene cycloadditions6ac and nucleophilic additions,6d,e despite their known tendency to dimerize or oligomerize 7. 8 Hydrazones6bd and hydrazides6a,e are bench‐stable, convenient “blocked” N ‐substituted isocyanate precursors9 that form the desired isocyanates via an equilibrium induced under mild conditions, and then react with nucleophiles such as amines, alcohols, and thiols 6de. Using this reactivity, we developed a cascade substitution/hydroamination sequence allowing rapid assembly of saturated nitrogen heterocycles from hydrazide starting materials 6e.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Recently, methods for the generation of cyclic azomethine imines I were explored, including the [3+2] cycloaddiiton of norbornene 4 and hydrazones 5 (Scheme 2). [7] This synthesis of azomethine imines was believed to proceed via a concerted alkene aminocarbonylation pathway, where the formation of amino-isocyanate intermediate 6 through the removal of phenol or tert-butyl alcohol was proposed as the key step. An Guanyinsheng Qiu was born in Jiangxi (China) unsymmetrical aminocarbonylation of alkene was also developed for the synthesis of N,N-cyclic azomethine imines possessing the b-aminocarbonyl motif (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%